Education on the rails: a textual ethnography of university advertising in mobile contexts. Issue 2 (4th May 2017) - Symes, Colin; Drew, Christopher
ABSTRACT: As universities have succumbed to market discourses, they have adopted advertising strategies. It is not uncommon to see advertisements for them displayed in such mobile spaces as railway stations and alongside highways. Whilst it is true that such environments have always sought to take advantage of populations in transit, the fact that higher education institutions have turned to them as promotional sites, reflects the fact that the 'transit' demographic now includes large numbers of young people and high school students. In this paper, a sample of higher education advertisements found in Sydney's transit spaces is analysed along with the 'rationale' provided by advertising companies responsible for their design. It is argued their existence reflects the fact that universities compete against one another for students and need to develop a persuasive 'brand'. Thus in line with neo-liberalist constructions of subjectivity, they individualise the educational experience, and translate that experience into an economic asset, as a value-adding process. It is of note then that much of the imagery and copy of the advertising 'visualises' education as a journey and underpins the fact that mobility is an inescapable predicate of quotidian life.